2013
DOI: 10.1037/a0034381
|View full text |Cite
|
Sign up to set email alerts
|

How are top companies assessing their high-potentials and senior executives? A talent management benchmark study.

Abstract: Although high-potential and executive assessment has been a popular topic in practice for decades, the primary emphasis in the literature has been on the development and use of specific tools and interventions. As a result, when organizations seek guidance on the practice of assessment in corporations, Industrial-Organizational psychology (I-O) practitioners and consulting psychologists have limited information available with which to compare. Moreover, industry reports often represent a specific tool, techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 31 publications
9
102
2
Order By: Relevance
“…TM decisions are not only influenced or biased by those making the decisions, but also by the specific instruments used to make decisions. The psychometric qualities of different measurement methods (e.g., self-and other-ratings versus standardized tests) seem to differ widely depending on the context in which they are administered (Church & Rotolo, 2013). Informed by these insights we advise TM scholars and practitioners to study the psychometric qualities of different TM instruments and measures and this within the contextual boundaries in which they are applied, a practice largely absent in the current body of literature.…”
Section: Recommendations For Research and Practicementioning
confidence: 99%
See 2 more Smart Citations
“…TM decisions are not only influenced or biased by those making the decisions, but also by the specific instruments used to make decisions. The psychometric qualities of different measurement methods (e.g., self-and other-ratings versus standardized tests) seem to differ widely depending on the context in which they are administered (Church & Rotolo, 2013). Informed by these insights we advise TM scholars and practitioners to study the psychometric qualities of different TM instruments and measures and this within the contextual boundaries in which they are applied, a practice largely absent in the current body of literature.…”
Section: Recommendations For Research and Practicementioning
confidence: 99%
“…The third most prevalent framework is employee assessment, with 11.5% of coded articles (16 articles) sorting under 'employee assessment' as a primary (4 articles; 2.8%) or secondary (12 articles; 8.6%) framework. In TM articles with an employee assessment framework, the focus tends to lie on identifying leadership talent, while much less research is found mentioning other 'types' of talent employees may possess (Church & Rotolo, 2013). The demonstration of predictive validity requires addressing the following question-do those identified as talented early on exhibit excellent performance at a later point in time, in a more advanced position (Nijs et al, 2014)?…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The success of any organization heavily relies upon effective and outstanding leaders. Succession planning consists the process of looking a suitable potential candidate for future leader and career development (Dessler, 2004;Rothwell, 2010;Church and Rotolo, 2013) Therefore, the career path of subordinate can be managed to fulfill the organizational need's and the subordinate's inspiration. Moreover, the implementation of succession planning towards subordinate is closely linked to a leader's leadership style.…”
Section: International Journal Of Asian Social Sciencementioning
confidence: 99%
“…Typically, the most common-methods of identifying high potential employees are: a) the opinions of senior leaders, b) performance appraisal, or c) a talent review process (Church & Rotolo, 2013). The identification of high potential employees is rarely classified using 360 feedback (16%), psychological testing (14%), cognitive testing (9%), assessment centers (7%), or simulations (4%).…”
Section: Learning Agility and Potentialmentioning
confidence: 99%